Stroke in Saudi Arabia: a review of the recent literature - Robert, Asirvatham Alwin (The African Field Epidemiology Network, 2014)
Stroke is a major cerebrovascular disease resulting in high mortality and persistent disability in adults across the world. Besides coronary heart disease and cancer, stroke is the commonest cause of death in most industrialized countries. Survivors of stroke are often left with severe mental and physical disabilities, which create a major social and economic burden, ranking as the second most common cause of death worldwide and a major source of morbidity. The Kingdom of Saudi Arabia (KSA) is the largest country in the Middle East occupying approximately four-fifths of the Arabian Peninsula supporting a population of more than 28 million. Stroke is becoming a rapidly increasing problem and an important cause of illness and deaths in Saudi Arabia. However, compared with the developed countries, research regarding the incidence, prevalence and their socio-demographic properties of stroke is still insufficient due to lack of appropriate studies being conducted in these specified areas. This review aims to discuss the range of the aspect of stroke in Saudi Arabia from the literature published.